Development of Motoric Skills Through Sensory Play Stimulation in Preschool Children - Putri, Dhea Natasya; Abiddin, Andi Hayyun; Galabay, Jolo (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Motoric development is an essential aspect of child development, even said to be the first benchmark to see the growth and development of children. One of the assessments of motoric development can be done with the sensory play method. This study aims to identify children's fine motor development through the sensory play method. This research method is a descriptive research design. The sample in this study was all children aged 4-7 years who attended Kindergarten “Dharma Wanita Kotes” in January - March 2023 with a total population of 25 students. The sampling technique used total population sampling. Data collection uses a checklist sheet, assessment according to interpretation guidelines. The results showed the development of seven senses of children through sensory play methods such as the senses of sight, hearing, smell, taste, touch, all respondents developed according to age (100%), but in the development of the senses of touch, vestibular and proprioceptive, almost all respondents developed (96%) , because there is one respondent who has difficulty when playing activities with the seven senses, where this is influenced in terms of age and lack of socializing.